Zircon U–Pb ages, geochemistry, and Nd–Hf isotopes of the TTG gneisses from the Jiaobei terrane: Implications for Neoarchean crustal evolution in the North China Craton. (February 2015) - Shan, Houxiang; Zhai, Mingguo; Wang, Fang; Zhou, Yanyan; Santosh, M.; Zhu, Xiyan; Zhang, Huafeng; Wang, Wei
Highlights: The TTG gneisses in Jiaobei formed at 2508–2547 Ma. TTG magma at ∼2.5 Ga is more widely distributed vertically than that of ∼2.7–2.9 Ga. The Jiaobei TTGs originated from partial melting of subducted slab in continental arc. The most likely source might have been rutile-bearing amphibole eclogite. ∼2.5 Ga magmatism represents a coherent event of crustal growth and reworking. Abstract: The Precambrian basement in the Jiaobei terrane is largely composed of Tonalite–Trondhjemite–Granodiorite (TTG) suite of rocks and offers important insights into the crustal evolution history of the North China Craton (NCC). The LA-ICP-MS zircon U–Pb age data presented in this study show that the magmatic protoliths of the TTG gneisses formed during 2508–2547 Ma and recorded the Paleoproterozoic metamorphism (∼1905 Ma). The rocks are enriched in LILE (Rb, Ba and Sr) and depleted in HFSE (Nb, Ta, Zr and Hf). They are characterized by high Sr contents (406–2906 ppm), Sr/Y ratios (31.3–355) and subchondritic Nb/Ta ratios (18.5–68.9). The TTGs show relatively high ΣREE contents (72.0–266 ppm) with strongly enriched LREE ((La/Yb)N  = 11.5–121) and positive or negligible negative Eu anomalies (Eu/Eu ∗  = 0.84–1.89). These geochemical features suggest that the magma source might have been rutile-bearing amphibole eclogite. Their high Mg # numbers (42–56) and high Cr (153–285 ppm) and Ni contents (22.2–74.5 ppm) indicate interaction with the mantle wedge during magma ascent. The whole rock ε Nd ( t ) values (+2.6 to +3.8) and most of the magmatic zircon ε Hf ( t ) values (+1.3 to +7.6) suggest juvenile to evolved isotopic signatures. All these lines of evidence suggest that the TTG rocks in this study formed through partial melting of subducted oceanic slab in a continental arc environment. The drill holes in the Jiaobei terrane are dominated by ∼2.5 Ga TTG gneisses, suggesting that the TTG magma at ∼2.5 Ga is more widely distributed deep underground than that of ∼2.7–2.9 Ga, at least within the approachable depth range of our research. Some zircon grains from Jiaobei TTGs give high ε Hf ( t ) values plotting above the curve of 0.75 ∗  ε Hf of DM, and their T C DM ages are very close to the time of the zircon crystallization. However, the majority of the ε Hf ( t ) values fall below the curve of 0.75 ∗  ε Hf of DM and their T C DM ages are concentrated between ∼2.7–2.9 Ga. Therefore, combining with other related studies, we propose that the ∼2.5–2.6 Ga magmatism in the NCC probably represents a coherent event of crustal growth and major reworking (remelting).